Pengembangan Stadiometer sebagai Alat Ukur Tinggi Badan dan Tinggi Lutut - S Sulistyawati (UPT Laboratorium Terpadu, Universitas Diponegoro, 2019)
Anthropometric measurement used to describe the conditions of growth and nutritional status. Linear growth is used to determining height with microtoise several requirements for its installment such as upright wall, flat floor and requires precision to ensure the starting point of measurement at 200 cm high, which making measurements with this method difficult to guarantee validity in field. This study aimed to make a height measuring instrument more practical, namely the modifiable stadiometer as a measuring instrument for height which can also be used to measure knee height. Material used aluminum to make the tool lighter, practical, and easy to carry. Validity test of tool was using stadiometer Seca 217. Height measurement was performed on 75 subjects in 7th semester students (academic year of 2015/2016) at Faculty of Public Health, University of Diponegoro Semarang. Data were analyzed by using paired t-test at significance level of 0.05 and obtained p=0.173. It was concluded that there was no significant difference in measurement results between modifiable stadiometer tool (the design results) and stadiometer Seca 217, so it can be used as alternative tool for height measurement.